1999
DOI: 10.1074/jbc.274.16.11399
|View full text |Cite
|
Sign up to set email alerts
|

A Silencer Element in the Regulatory Region of Glutamine Synthetase Controls Cell Type-specific Repression of Gene Induction by Glucocorticoids

Abstract: Glutamine synthetase is a key enzyme in the recycling of the neurotransmitter glutamate. Expression of this enzyme is regulated by glucocorticoids, which induce a high level of glutamine synthetase in neural but not in various non-neural tissues. This is despite the fact that non-neural cells express functional glucocorticoid receptor molecules capable of inducing other target genes. Sequencing and functional analysis of the upstream region of the glutamine synthetase gene identified, 5 to the glucocorticoid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…pUAS66GRE contains a fragment of 66 bp inserted between the UAS and GRE sequence in pUASGRE. The fragment was derived from a subclone of the previously described p2.4GS construct (1) and includes the sequence that spans between nucleotides 528 and 572 in the promoter of avian glutamine synthetase (GenBank TM accession number AF105022). pRepUASGRE was constructed by replacing the CMV promoter in the pCEP4 vector (Invitrogen) with the UAS-GRE-TK promoter and the adjacent luciferase gene derived from pUASGRE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…pUAS66GRE contains a fragment of 66 bp inserted between the UAS and GRE sequence in pUASGRE. The fragment was derived from a subclone of the previously described p2.4GS construct (1) and includes the sequence that spans between nucleotides 528 and 572 in the promoter of avian glutamine synthetase (GenBank TM accession number AF105022). pRepUASGRE was constructed by replacing the CMV promoter in the pCEP4 vector (Invitrogen) with the UAS-GRE-TK promoter and the adjacent luciferase gene derived from pUASGRE.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of glucocorticoid inducible genes may also be determined by transcriptional repressors that block the hormonal response. This latter type of action is exerted, for example, by the neural restrictive silencing factor NRSF/REST, which is expressed in non-neural tissues and can restrict the hormonal induction of avian glutamine synthetase to neural tissues (1). The molecular mechanism that underlies the interplay between GR and negative or positive transacting factors is largely unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two broad regions mediating this response have been identified in the upstream promoter and in the first intron of GS. Detailed studies of GS expression in chicken brains showed that glucocorticoids act by relieving the repression mediated by a silencer element located upstream of the glucocorticoid receptor binding site (5). This glucocorticoid-mediated induction of GS occurs particularly in conditions of trauma or high catabolic rate and results in increased glutamine synthesis at the expense of the AA that purvey the amino groups.…”
Section: A Introductionmentioning
confidence: 99%
“…In rainbow trout, the highest level of GS expression occurs in the brain, with decreasing levels in intestine, liver, red muscle, gill/kidney, white muscle, and heart (Murray et al, 2003). GS expression is high in neural tissues and in post-blood-fed female A. aegypti mosquito midguts, in which it is involved in peritrophic matrix formation (Avisar et al, 1999;Smartt et al, 2001). In plants, the evidence reported herein indicates that the pine GS gene family contains at least two isoforms that have unique and precise patterns of spatial and temporal expression, suggesting that they play distinct functional roles in nitrogen metabolism of conifers (Avila et al, 2001).…”
Section: Discussionmentioning
confidence: 99%